Carmen, a mulher vestida da lua: erotismo e sexualidade, de Prosper Mérimée a Vicente Aranda - Carvalho, Sueleny Ribeiro (2018)
Over this research, I analyze the representation modes of the Carmen character in narrative of the same name by Prosper Mérimée and in the film Carmen, by Vicente Aranda, in order to understand the mechanisms used for the construction of the character. In this work, my objective is to discuss the process of representing women from the analysis of the two works, the literary and the cinematographic one, considering the process of knowledge production that establishes the difference of gender from the sexual difference and that contributed to the fixation of the image of women by sexuality. Therefore, from the analysis of the representation of the character, I plan to establish a relation between this form of representation and the ideological structure of the dominant thought responsible for the construction of the image of women as a devil, fixed both in the production of fiction and in concrete social relations. The methodology uses the procedures of comparative literature, both about the corpus that constitutes the research – the literary text and the film adaptation – and about the theory that bases the research through the appropriation of theories distributed in other areas of knowledge besides literature, such as anthropology, philosophy, history and psychoanalysis. I think the possible flexibility between areas of knowledge, especially from cultural studies, that allows us to approach different concepts and to unravel the ideological structures behind them, as well as to deconstruct and to give new meaning to truths that until recently seemed absolute, such as the notions of eroticism and identity.